1991
DOI: 10.1159/000173412
|View full text |Cite
|
Sign up to set email alerts
|

The Munich Wistar Frömter Rat: Proteinuria and Blood Pressure in Correlation to the Number of Superficial Glomeruli

Abstract: Rats with a high number of superficial nephrons (MWF/Ztm) also show an elevated urinary protein excretion and a high systolic blood pressure. To investigate a possible correlation between the number of superficial glomeruli and these physiological changes, MWF/Ztm rats were crossed and backcrossed to Wistar cryptorchic (WC/Ztm) animals with no superficial nephrons in order to produce genotypes with differing numbers of superficial glomeruli. In the parental strains, the F1 hybrids and the 8 possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…One drawback, however, is that MWF rats not only have a desirable high percentage of superficially located glomeruli, they also show a reduced nephron number when compared to other commonly used strains such as Sprague Dawley or Wistar rats [17]. As a model of low nephron number, ageing MWF rats develop hypertension, progressive glomerulosclerosis, proteinuria, and, eventually, deterioration of renal function [6], [7], [17]. For reasons that are not entirely clear, the renal phenotype of MWF rats is more pronounced in male than female rats, making females more suitable for use in studies assessing the structure and function of the kidney and, more specifically, of the glomerulus [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One drawback, however, is that MWF rats not only have a desirable high percentage of superficially located glomeruli, they also show a reduced nephron number when compared to other commonly used strains such as Sprague Dawley or Wistar rats [17]. As a model of low nephron number, ageing MWF rats develop hypertension, progressive glomerulosclerosis, proteinuria, and, eventually, deterioration of renal function [6], [7], [17]. For reasons that are not entirely clear, the renal phenotype of MWF rats is more pronounced in male than female rats, making females more suitable for use in studies assessing the structure and function of the kidney and, more specifically, of the glomerulus [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MPM imaging of the glomerulus and the JGA has primarily been performed in Munich-Wistar-Froemter (MWF) rats, a rat strain that features many superficially located glomeruli [5], [6]. However, the use of MWF rats in kidney research is problematic, because this rat strain suffers from progressive deterioration of kidney function, due to the development of proteinuria, glomerulosclerosis, and hypertension [5], [6], [7], [8], [9]. In mice, MPM imaging of superficially located glomeruli has been reported in intact BL/6 mouse kidneys, but imaging has been preferentially performed in the kidneys of young animals because the number of glomeruli close to the kidney surface decreases considerably as the organ grows [10].…”
Section: Introductionmentioning
confidence: 99%
“…The epithelial cells lining Bowman's capsule appear to have an important role in matrix deposition in glomerular injury. 29 Electron microscopic examination of the glomerulus in a number of species has shown that there is a single basement membrane in the capillary tuft with fenestrated endothelium on the side of the circulation and visceral epithelial cells on the side of the filtrate. 27 In adult laboratory animals the number and size of glomeruli are a relatively constant function of body weight.…”
Section: Glomerulusmentioning
confidence: 99%
“…As a model of low nephron number, MWF rats gradually develop glomerulosclerosis, hypertension, and proteinuria (Remuzzi et al, 1988;Hackbarth et al, 1991). An in vivo inspection of the morphology of the glomeruli of 9-week-old MWF rats revealed no apparent abnormalities (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their high number of superficial glomeruli, MWF rats are particularly suited for the investigation of glomerular function by MPM, and, similarly, by micropuncture (Hackbarth et al, 1983). For the investigation of the normal function of the glomerulus, however, only young MWF rats appear to be suitable because aged MWF rats develop hypertension, proteinuria, and glomerulosclerosis (Hackbarth et al, 1991). This pathology is most likely related to the low nephron number of this rat strain (Rothermund et al, 2011).…”
Section: Discussionmentioning
confidence: 99%